"Never Anything About the Asian Experience": An AsianCrit Analysis of Asian American Teachers in the Midwest. (3rd April 2022) - Kim, Jung
Abstract : Although Asian Americans are the fastest-growing racial minority group in the United States, projected to be 10% of the population by 2050, they only comprise 2% of the teaching force. There is relatively little research about the experiences, recruitment efforts, or retention of Asian American teachers. This qualitative study seeks to add to the extant literature by seeking to better under the experiences of Asian American pK-12 teachers in the Midwest, primarily in northern Illinois. This study draws upon both a sociopolitical understanding of being Asian American and three specific tenets of AsianCrit: (re)constructive history; story, theory, and praxis; and commitment to social justice to understand how Asian American teachers in the Midwest navigate teaching and learning in the classrooms as racialized beings.